Emotional Resonance and Buying Behavior in Live Streaming: A Study on KOL Influence and the Mediation of Purchase Intentions - Jinpeng Wen; Xiaohua Li; Hongxing Han (Journal of Theoretical and Applied Electronic Commerce Research)
This study aims to explore how key opinion leader (KOL) characteristics influence users’ purchase intentions in live shopping. Using a mixed-methods approach, the study combines real-time pop-up text mining and questionnaires, analyzed via Latent Dirichlet Allocation (LDA) topic modeling and a research framework integrating the stimulus–organism–response (SOR) model with pleasure–arousal–dominance (PAD) theory. Results indicate that KOL characteristics—namely professionalism, popularity, attractiveness, and entertainment—enhance users’ pleasure, arousal, and trust. These emotions boost impulse buying intentions but not planned ones. Planned purchase intention acts as a partial mediator, whereas impulse purchase intention serves as a full mediator. This research uncovers the intricate mechanism linking KOL traits to user emotions and purchase intentions. By integrating PAD theory and the SOR model, it examines emotional mediators, addresses prior theoretical gaps, offers vital insights for refining live-streaming marketing strategies, and holds substantial theoretical and practical significance for the sustainable growth of live-streaming e-commerce.